Research on Plasma-Synergized Catalytic Ammonia Synthesis Based on Supported SBA-15 Catalysts - Jinfei CHEN; Xuesen DU; Xiaojun SU; Chaofan LI; Xiaoqiang SHEN; Chenlong HU (能源环境保护)
Plasma-catalytic ammonia synthesis has garnered significant attention due to its potential for reducing energy consumption and mitigating environmental impact, emerging as a promising alternative to traditional thermal catalytic ammonia synthesis processes. Developing efficient catalysts to enhance the synergy between plasma and catalytic materials remains a key challenge. This study experimentally investigated a series of supported SBA-15 catalysts (M/SBA-15, M = 5Fe, 5Co, 5Ni, 10Ni, and 15Ni) to examine the process of plasma-enhanced ammonia synthesis. The initial characterization results indicated that the active metal species in all catalysts were present as metallic elements and oxides, both on the catalyst surface and within the pores, exhibiting uniform dispersion. Activity tests revealed that catalytic performance was not correlated with the specific surface area of the catalysts; rather, the inherent ammonia synthesis properties of the active metal species had a more significant impact. Notably, Ni-based catalysts exhibited superior catalytic activity compared to those based on Fe and Co. Further investigation into the ammonia synthesis activity of catalysts with varying Ni loadings revealed a volcano-shaped curve in plasma-assisted ammonia concentration, which initially increased and then decreased with increased Ni loading. Specifically, increasing the Ni loading from 5% to 10% improved ammonia synthesis performance by 8.0%, while further increasing the Ni loading to 15% led to a 3.3% decrease in performance. This relationship implied that a critical Ni loading threshold existed, above which excessive Ni loading could damage the catalyst's pore structure or cause surface poisoning. Subsequently, the discharge characteristics of the 10Ni/SBA-15 catalyst, which exhibited the highest ammonia synthesis performance, were analyzed. The results revealed a transition in discharge mode from filamentary discharge to a combination of filamentary and surface discharge, in contrast to an empty tube. This transition led to a more uniform and stable discharge state, with higher average current values within the clusters. The enhanced discharge state promoted the generation of more high-energy electrons and excited-state species, such as \begin{document}${N}_2^* $\end{document}, \begin{document}${H}_2^* $\end{document}, and NHx (x=1, 2), which are essential for ammonia synthesis, thereby significantly improving ammonia production. Stability tests demonstrated that catalyst activity rapidly decreased during the first 180 minutes, followed by stabilization, emphasizing the importance of preserving the catalyst's pore structure for prolonged catalytic activity. Finally, the plasma-assisted ammonia synthesis performance of the catalyst was evaluated for ammonia concentration and energy yield. The evaluation results indicated that, in comparison to related cutting-edge research, this study achieved ammonia concentrations as high as 9 927 mg/m³ and an energy yield of 0.88 g/(kW·h) with the 10Ni/SBA-15 catalyst, showcasing significant competitiveness. These findings contribute to understanding the plasma catalytic process and provide new insights into the design of efficient catalysts for plasma-assisted ammonia synthesis.